Nociceptive Sensory Fibers Drive Interleukin-23 Production in a Murine Model of Psoriasis via Calcitonin Gene-Related Peptide - Zhang, Xuan; Cao, Jiali; Zhao, Siqi; Yang, Xutong; Dong, Jie; Tan, Yaqi; Yu, Teng; He, Yanling (Frontiers in Immunology, 2021)
Neuroimmunity is involved in the pathogenesis of psoriasis, but the mechanism underlying the interaction between the nervous system and the interleukin (IL)-23/IL-17 immune axis is yet unclear. This study reveals the essential role of the sensory neuron-derived calcitonin gene-related peptide (CGRP) in imiquimod (IMQ)-induced expression of IL-23. First, we show that the increased nociceptive behavior was consistent with the development of psoriasiform dermatitis, which requires intact sensory innervation. Systemic ultrapotent Transient receptor potential vanilloid 1 (TRPV1) agonist (resiniferatoxin, RTX) treatment-induced sensory denervation resulted in a significant decrease in IL-23 expression in this model, while the recombinant IL-23 treatment induced IL-17A expression was intact after RTX treatment. In addition, IMQ exposure induced a transient increase in CGRP expression in the dorsal root ganglion. The neuron-derived CGRP expression was completely abolished by sensory denervation, thereby downregulating IL-23 expression, which could be reversed through the introduction of CGRP into the denervated dorsal skin. Our results suggest that nociceptive sensory neurons may drive the production of IL-23, resulting in IL-17A production from γδ T cells via the neuropeptide CGRP in the pathology of psoriasis.